Transcarotid Mechanical Thrombectomy for Embolic Intracranial Large Vessel Occlusion after Endovascular Deconstructice Embolization for Carotid Blowout Syndrome - Chi-Ju Lu (Neurointervention, 2020)
Carotid blowout syndrome (CBS) is a fatal complication of head and neck cancer. Endovascular treatment, particularly deconstructive embolization, is effective for CBS, but it might result in thromboembolic events. We report the case of a 57-year-old man with underlying recurrent head and neck cancer who had CBS. The patient received endovascular embolization of the right internal, external, and common carotid arteries. Right internal carotid artery to middle cerebral artery embolic occlusion was noted immediately after the procedure, and left-sided weakness and facial palsy were found. Ipsilateral suprabulbar cervical internal carotid artery puncture was performed under fluoroscopic guidance, and rescue suction thrombectomy was successful. The patient had no significant neurological sequela. Transcarotid intraarterial thrombectomy is a reasonable method for managing postembolization large vessel occlusion, even in the neck, after irradiation.